Experimental characterization of a long counter for neutron fluence measurement. (December 2018) - Hu, Z.M.; Peng, X.Y.; Chen, Z.J.; Du, T.F.; Ge, L.J.; Yuan, X.; Cui, Z.Q.; Zhu, W.J.; Wang, Z.M.; Zhu, X.; Chen, J.X.; Li, X.Q.; et al.
Abstract: A De Pangher-type long counter was constructed at Peking University for neutron fluence measurement. The responses and effective centers of the long counter were calculated using the Monte Carlo method. The variations with neutron energy of the position of the effective center, calculated by the Monte Carlo code, was experimentally validated with a 241 AmBe neutron source and several mono-energetic neutron sources ranging from 100 keV to 6 MeV. Long counter calibration was performed using a radionuclide source from Peking University, and neutron fluence measured by the calibrated long counter was successfully compared to values determined with reference instruments (two recoil proton counters and a 238 U fission chamber). The relative deviations were lower than 6% along the whole energy range. The calibrated long counter was thus successfully applied in the calibration of a Bonner sphere spectrometer. Highlights: A new long counter was constructed at Peking University making up for the lack of devices for neutron fluence measurement from 1 MeV to 2 MeV. The Monte Carlo method using three source models were employed to calculate response values. The effective centers were calculated in detail using random method at 149 energy points. The response and effective center values were experimentally evaluated by 8 neutron sources and good agreement between the calculations and experiments were found.